FUNDAMENTAL INAPPROPRIATENESS OF MANAGEMENT IN THE SYSTEM OF MEDICAL CARE FOR THE POPULATION OF UKRAINE - Журавель, Володимир; Білоус, Василина; Журавель, Віктор; Журавель, Володимир (SWorldJournal, 2025)
The article highlights issues of fundamental and organizational-methodological inconsistencies in practical management within the healthcare system for the population of Ukraine, considering both systemic and competency-based approaches, as well as pers